2019
DOI: 10.1136/bmjdrc-2018-000632
|View full text |Cite
|
Sign up to set email alerts
|

Individual free fatty acids have unique associations with inflammatory biomarkers, insulin resistance and insulin secretion in healthy and gestational diabetic pregnant women

Abstract: ObjectiveWe investigated the relationships of maternal circulating individual free fatty acids (FFA) with insulin resistance, insulin secretion and inflammatory biomarkers during mid-pregnancy.Research design and methodsThe data were drawn from a prospective cohort of generally healthy pregnant women (n=1368, African-American 36%, Hispanic 48%, Caucasian 16%) in Camden, NJ. We quantitatively determined 11 FFAs, seven cytokine/adipokine, homeostatic model assessment of insulin resistance (HOMA-IR) and C-peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 46 publications
5
39
0
1
Order By: Relevance
“…Elevated blood levels of FFA also resulted in the up to 47% diminution of insulin-stimulated glucose uptake and glycogen synthesis [136]. More recently, the relationship of maternal individual FFA level with GDM and inflammatory response has also been studied [137]. This study indicated a positive relationship of palmitic, stearic, dihomo-γ-linolenic (DGLA), and arachidonic acids with the C-peptide level, cytokines/adipokines, and GDM.…”
Section: Biomarkers Of Disturbed Lipid Metabolismmentioning
confidence: 86%
“…Elevated blood levels of FFA also resulted in the up to 47% diminution of insulin-stimulated glucose uptake and glycogen synthesis [136]. More recently, the relationship of maternal individual FFA level with GDM and inflammatory response has also been studied [137]. This study indicated a positive relationship of palmitic, stearic, dihomo-γ-linolenic (DGLA), and arachidonic acids with the C-peptide level, cytokines/adipokines, and GDM.…”
Section: Biomarkers Of Disturbed Lipid Metabolismmentioning
confidence: 86%
“…Indeed, some studies in humans have observed correlations between inflammatory markers and specific FFAs. For example, in a prospective study involving women with or without gestational diabetes [136], inflammatory markers were inversely correlated with palmitoleic, oleic, linolenic, and myristic acids, whilst positive associations were found with palmitic, stearic, arachidonic, dihomo-γ-linolenic, and docosahexaenoic acids.…”
Section: Ffa Metabolism In T2dmmentioning
confidence: 99%
“…A study by Chen et al [ 76 ] of pregnant women with GDM found a positive correlation between palmitic, stearic, AA, and DGLA with the insulin resistance index and C-peptide level. This strongly confirms the impact of saturated fatty acids and AA and DGLA on the occurrence of IR.…”
Section: Participation Of Aa Metabolites In Pregnancymentioning
confidence: 99%